Identification and expression of troponin T, a new marker on the surface of cultured tumor endothelial cells by aptamer ligand. (9th May 2014) - Ara, Mst. Naznin; Hyodo, Mamoru; Ohga, Noritaka; Akiyama, Kosuke; Hida, Kyoko; Hida, Yasuhiro; Shinohara, Nobuo; Harashima, Hideyoshi
Abstract The identification of a specific biomarker involves the development of new clinical diagnostic tools, and an in‐depth understanding of the disease at the molecular level. When new blood vessels form in tumor cells, endothelial cell production is induced, a process that plays a key role in disease progression and metastasis to distinct organs for solid tumor types. The present study reports on the identification of a new biomarker on primary cultured mouse tumor endothelial cells (mTECs) using our recently developed high‐affinity DNA aptamer AraHH001 (Kd = 43 nmol/L) assisted proteomics approach. We applied a strategy involving aptamer‐facilitated biomarker discovery. Biotin‐tagged AraHH001 was incubated with lysates of mTECs and the aptamer‐proteins were then conjugated with streptavidin magnetic beads. Finally, the bound proteins were separated by sodiumdodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) with silver staining. We identified troponin T via matrix assisted laser desorption ionization‐time of flight (MALDI‐TOF) mass spectrometry, the molecular target of aptamer AraHH001, and its presence was confirmed by measuring mRNA, protein levels, western blot, immunostaining, a gel shift assay of AraHH001 with troponin T. We first report here on the discovery of troponin T on mTECs, a promising and interesting diagnostic tool in the development of antiangiogenic therapy techniques the involves the targeting of the tumor vasculature.